PERLINDUNGAN HAK-HAK KELUARGA DALAM AL-QUR'AN: PERSPEKTIF ADVOKASI ISLAM - Nazri Arif, Nurhilal; Rahmani, Ilham; Ismail, Hidayatullah (CV. Lafadz Jaya, 2025)
The family is the most fundamental social institution in society, serving as a place for the education of values, love, and protection (Nasaruddin Umar, 1999). However, in reality, many of the rights of family members are ignored or even violated. The Qur’an, as the primary source of Islamic teachings, places great emphasis on the protection of rights within the family, including those of husbands, wives, children, and other relatives (M. Quraish Shihab, 2002). This study aims to examine the concept of protecting family rights in the Qur'an through an Islamic advocacy approach, namely how these scientific values can be implemented in the context of modern social-humanitarian issues. The method used is library research with qualitative analysis of relevant Qur'anic verses and the views of classical and contemporary exegetes (Harun Nasution, 1985). The results of the study show that the Qur'an emphasises the principles of justice, compassion (rahmah), and social responsibility as the main foundations of family protection (Sayyid Qutb, 2000). In addition, Islamic advocacy plays an important role in fighting for and protecting these rights, whether through educational, social, or legal approaches. This study recommends the integration of Qur’anic values into family social advocacy to create family resilience and justice in contemporary Islamic society.